Primary Care, Weather, and the Missed Opportunity for Savings - Maranna Yoder; Nilesh Shinde; Guangqing Chi; Seth Freedman; Kosali Simon; Sonia Angell (Health Affairs Scholar, 2026)
Abstract Extreme weather is a recurring source of stress on healthcare delivery, yet health systems remain largely reactive. Unlike an individual medical emergency, which the system absorbs one case at a time, a heat wave, wildfire smoke episode, or storm affects an entire population simultaneously. The resulting surge degrades care for every emergency patient, not only those the weather directly harmed. Primary care that anticipates weather-related risk and intervenes proactively can blunt that surge, but a central barrier to scaling such care is economic rather than clinical. Conventional prevention accounting counts only the benefit to the treated patient, and fee-for-service payment offers primary care practices only limited and poorly matched means to fund anticipatory care. Payment models that reward keeping patients healthy, such as global budgets, can address this, but only if risk adjustment accounts for environmental exposure so that providers serving vulnerable populations are not penalized. To address this, we outline four priorities: evaluations that capture system-wide costs; payment that rewards anticipatory care and adjusts for environmental risk; supply-side resilience in primary care, built jointly with public health agencies; and data infrastructure linking exposure to healthcare utilization.